(untitled) (Journal of Architectural Design, 2024)
Currently, issues related to preservation and repair of historical monuments are considered important in our country. This article provides a priority analysis on this topic. Thousands of monuments and monuments have appeared in our country. Much attention is paid to their maintenance and repair, as well as to the processes of repairing and creating objects. In the article, the topic "Study of the technical condition of the Somonii mausoleum and creation of a model on the basis of computer software, testing of its static and dynamic loads and evaluation of its technical condition" is considered as a priority. 3D models of the mausoleum were created and its effects on dynamic and static loads were analyzed in a computer program. At the same time, information technologies are important in studying the stress-deformation state of the architectural monument, applying dynamic and static loads to them and analyzing their results, and the research in this direction is widely seen in the article. . The scientists who have found their place have expressed their opinions about the bricks and mixes of the architectural monument, their mechanical and durability indicators. On the subject of this article, studies have been carried out due to the fact that scientific and research works aimed at protecting historical architectural monuments and revealing them to new generations are very important in our country